A study of iron removal from Sabah montmorillonite by extracting with organic acid - Samsuri, Ariffin; Irawan, Sonny (2004)
The removal of iron from Sabah montmorillonite mineral with three organic acids (citric, gluconic and oxalic) has been studied under various experimental conditions in order to optimise the process parameters and reach a high degree of iron removal at minimum operating cost. The parameters studied were: temperature, pH of the solution, organic acid concentration and time of leaching process. For the Sabah montmorillonite sample used, at temperature varying between 60-80oC the maximum iron extraction especially with oxalic acid that can achieved is approximately 90%. Oxalic acid is capable of dissolving all the extracted iron in montmorillonite, thus making the montmorillonite suitable for its basic industrial application. Iron dissolution is significantly affected by the pH, while it is practically independent of the oxalate concentration.Iron extraction is optimized in high acid solution, best results are achieved at concentration 7 kgm-3, pH less than 2, 80oC in temperature and 2 hours in stirring time.